Analisis Data Hasil Pemantauan Status Gizi dari Faktor Determinan Kejadian Stunting pada Balita - Hariani, Hariani; Sudarsono, I Made Rai; Sostinengari, Yeni (Poltekkes Kemenkes Kendari, 2018)
Short child problems (stunting) are one of the nutritional problems faced in the world, especially in poor and developing countries. Based on the results of the nutritional status assessment in 2016, the national nutritional status of children under five years old TB / U or PB / U in the stunting category reached 27.5% in Southeast Sulawesi Province, the prevalence of stunting under five reached 29.5%. Based on the results of the nutritional status assessment of the province of Southeast Sulawesi 2016, the prevalence of Konawe Regency reached 25.5% above the national prevalence. This study aims to determine the relationship between, parental height, exclusive breastfeeding, giving MP-ASI with stunting. This type of research is an observational study with the design of a cross-sectional study with a sample of 116 toddlers based on the analysis of nutritional status monitoring data in Konawe District, 2016. The independent variables in this study were exclusive breastfeeding, mother height, giving MP-ASI, and stunting as the dependent variable. The type of data used in this study is secondary data from the results of monitoring nutritional status in Konawe Regency of Southeast Sulawesi Province in 2016. Stunting prevalence in Konawe Kepualauan 2016 reached 28,5%. There is no relationship between Asi exclusively with stunting (p = 0.941). There was no relationship between maternal height and stunting (p= 1,000). There was no relationship between administration of MP-ASI with stunting (p = 0.941). There are no relationships between giving MP-ASI, maternal height exclusive, breastfeeding with the incidence of stunting.